Neurochemistry study of spinal cord in non-human primate (Sapajus spp.) - K.R. Torres-da-Silva; A.V. da Silva; N.O. Barioni; G.W.L. Tessarin; J.A. de Oliveira; E. Ervolino; J.A.C. Horta-Junior; C.A. Casatti (European Journal of Histochemistry, 2016)
The spinal cord is involved in local, ascending and descending neural pathways. Few studies analyzed the distribution of neuromediators in the laminae of non-human primates along all segments. The present study described the classic neuromediators in the spinal cord of the non-human primate Sapajus spp. through histochemical and immunohistochemical methods. Nicotinamide adenine dinucleotide hydrogen phosphate-diaphorase (NADPH-d) method showed neuronal somata in the intermediolateral column (IML), central cervical nucleus (CCN), laminae I, II, III, IV, V, VI, VII, VIII and X, besides dense presence of nerve fibers in laminae II and IX. Acetylcholinesterase (AChE) activity was evident in the neuronal somata in laminae V, VI, VII, VIII, IX, CCN, IML and in the Clarke’s column (CC). Immunohistochemistry data revealed neuronal nitric oxide synthase (nNOS) immunoreactivity  in neuronal somata and in fibers of laminae I, II, III, VII, VIII, X and IML; choline acetyltransferase (ChAT) in neuronal somata and in fibers of laminae VII, VIII and IX; calcitonin gene-related peptide (CGRP) was noticed in neuronal somata of lamina IX and in nerve fibers of laminae I, II, III, IV, V, VI and VII; substance P (SP) in nerve fibers of laminae I, II, III, IV, V, VI, VII, VIII, IX, X, CCN, CC and IML; serotonin (5-HT) and vesicular glutamate transporter-1 (VGLUT1) was noticed in nerve fibers of all laminae;  somatostatin (SOM) in neuronal somata of laminae III, IV, V, VI, VII, VIII and IX and nerve fibers in laminae I, II, V, VI, VII, X and IML; calbindin (Cb) in neuronal somata of laminae I, II, VI, VII, IX and X; parvalbumin (PV) was found in neuronal somata and in nerve fibers of laminae III, IV, V, VI, VII, VIII, IX and CC; finally, gamma-amino butyric acid (GABA) was present in neuronal somata of laminae V, VI, VII, VIII, IX and X. This study revealed interesting results concerning the chemoarchitecture of the Sapajus spp. spinal cord with a distribution pattern mostly similar to other mammals. The data corroborate the result described in literature, except for some differences in CGRP, SP, Cb, PV and GABA immunoreactivities present in neuronal somata and in nerve fibers. This could suggest certain specificity for the neurochemistry distribution in this non-human primate species, besides adding relevant data to support further studies related to processes involving spinal cord components.